System On Chip Design: Master Studies Experience And Prospective For Phd Studies In Macedonia - Trajanov, Dimitar; Filiposka, Sonja; Lazarevska, Marija; Grnarov, Aksenti (My University, 2009)
Embedded systems give intelligence to many devices that we use in everyday life – they are found in everything from mobile phones and MP3 players, over cars and home appliances, to complex controllers. The continuous progress of semiconductor technology has made it possible to implement complex systems on a single chip, which has led to new challenges in design methodologies. Driven by these technological forces, the Faculty of Electrical Engineering and Information Technologies (FEIT) – Skopje with support from TEMPUS JEP_41107_2006 Project 0 has developed an interdisciplinary Master of Science Programme on System-on-Chip design, which couples hardware and embedded software design principles. The programme aims to provide students with competence and skills for designing, analyzing and verifying embedded systems. In this paper, we describe the process of developing the curriculum, the study programme plan, as well as our plans for developing PhD studies in System on Chip Design.